Ex vivo drug response profiling guides therapy in a case of high-risk acute undifferentiated leukemia with PICALM::MLLT10 - Elena Mastrodicasa; Luca Pagliaro; Valentina Pierini; Valentina Bardelli; Mariateresa Giaimo; Raffaella Zamponi; Anna Montanaro; Katia Tragni; Roberta Arcaleni; Maria Speranza Massei; Ilaria Capolsini; Katia Perruccio; et al. (Haematologica)
Not available.